2018
DOI: 10.1186/s12877-018-0724-4
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and cognition at admission to the nursing home – a cross-sectional study

Abstract: BackgroundEarlier studies show that the main reasons for admission to long-term nursing home care are cognitive impairment and functional impairments of activities of daily life. However, descriptive evidence of mobility is scant. The aims of this study were to describe mobility at admission to nursing homes and to assess the association between mobility and degree of dementia.MethodsWe included 696 residents at admission to 47 nursing homes in Norway. Inclusion criteria were expected stay for more than 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 32 publications
5
57
0
Order By: Relevance
“…Our result is a novel finding requiring further investigation to elucidate. We also observed that age, general medical health, and dementia severity were negatively associated with physical performance, associations well known across populations [5,[7][8][9]41].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our result is a novel finding requiring further investigation to elucidate. We also observed that age, general medical health, and dementia severity were negatively associated with physical performance, associations well known across populations [5,[7][8][9]41].…”
Section: Discussionsupporting
confidence: 69%
“…People with dementia exhibit a greater decline in physical performance compared to cognitively healthy adults [9], and as dementia severity increases, physical performance progressively deteriorates [10]. However, this relationship is not as clear in NH residents as in community-dwelling older adults [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPPB is calculated from three components: (i) time to complete a 2.4, 3, or 4m walk at the participant's usual pace, (ii) time to rise from a chair five times, and (iii) the ability to stand for up to 10 s with feet positioned in each of three ways (a side-by-side position, semi-tandem position, and tandem position) (9). The SPPB has been adopted in multiple observational studies, with higher scores indicating a higher level of PF and lower scores predicting adverse outcomes such as decreased mobility (10), falls (11), loss of independence in activities of daily living (ADLs) (12), hospitalization (8), longer hospital stays (13), nursing home admission (14), and all-cause mortality (15). Moreover, previous research has suggested that the SPPB can detect body composition changes (16,17) and inflammation (18), and a total score ≤ 9 points can distinguish between vigorous and frail persons (19).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from Norway show that the difference in mobility level and physical performance, measured by the Short Physical Performance battery (SPPB), are surprisingly similar between patients who make contact with home based services for the first time (2), and patients who are admitted to nursing homes (3). Langeland et al (2019) investigated the effect of a home based rehabilitation model, termed "reablement", in home-dwelling, older adults with a recent functional decline who were applying for home based services (2).…”
Section: Introductionmentioning
confidence: 99%